Simulation of Hetero-junction (GaInP/GaAs) Solar Cell Using AMPS-1D - Dennai Benmoussa; M. Boukais; H. Benslimane (Журнал нано- та електронної фізики)
Photovoltaic conversion is the direct conversion of electromagnetic energy into electrical energy continuously. This electromagnetic energy is the most solar radiation. In this work we performed a computer modelling using AMPS 1D optimization of hetero-junction solar cells GaInP / GaAs configuration for p/n. We studied the influence of the thickness the base layer in the cell offers on the open circuit voltage, the short circuit current and efficiency.